Biogeochemistry of organic carbon in permafrost peatland waters : an experimental approach - Payandi-Rolland, Dahédrey (CCSD, 2020)
The anthropogenic emissions of carbon dioxide (CO2) into the atmosphere are held responsible for the current global warming experienced by the Earth. Given the amplified effect of warming in the northern regions, the main objective of this thesis is to assess the factors that could influence the organic matter (OM) degradation within a carbon-rich permafrost peatland. For this purpose, we studied the effect of biological and geochemical parameters, which are directly or indirectly influenced by climate change, on the degradation of OM. Field studies and experiments were carried out in discontinuous permafrost areas of Eastern Siberia and Sweden, along with laboratory experiments using substrates from these regions and from peatlands of NE Europe. Experiments were conducted as a function of temperature, bacterial biomass, OM origins, water bodies heterogeneity, vegetation type, freezing and thawing cycles, anoxic conditions and soil depths. The originality of this work consists in the combination of various (bio)geochemical analyses using both fieldwork and laboratory approaches linking the different systems controlling OM degradation in the natural environment (mainly microbiology and geochemistry). After an introduction dealing with possible positive feedback of OM degradation in northern peatlands on climate warming, the first chapter is dedicated to a general context giving an insight of the OM in the arctic region under climate change challenges and presenting all the techniques, analyses and methods employed for this thesis. The second chapter describes the three studied sites and the general fieldwork, which involved the study of OM behaviour during diel cycles. The third chapter tackles the origin of OM and the water bodies heterogeneity effect on the biodegradation of OM. The fourth chapter investigates the impact of freeze-thaw cycles of peatland water bodies on OM degradation during transitional periods, such as early spring and late autumn. Finally, the last chapter reports the result of aerobic and ...